Effect of chemical desulfurization on coal properties and sulfur structure based on microwave technology. Issue 5 (24th May 2022) - Zhou, Bingyi; Ge, Tao; Luo, Xiaoman; Wang, Zhaohui; Qiao, Yueyue; Cai, Chuanchuan; Xu, Jingyao
Abstract: Under the two frequency microwave conditions of 915 and 2450 MHz, orthogonal tests were designed to investigate the effects of organic acid reagent, microwave irradiation time, and mixing time of additives and coal samples on the desulfurization effect of coal. Results show that the effect of irradiation time on the experimental desulfurization efficiency under frequency microwave conditions is large and is the main factor. The desulfurization effect under 915 MHz microwave condition is better than 2450 MHz microwave condition. Two sets of experimental optimal coal samples were used for characterization and analysis. Thermogravimetric analysis revealed that the combustion temperature range of the coal samples is shortened and the integrated combustion index is considerably higher after the microwave irradiation experiment. Fourier‐transform infrared spectroscopy analysis showed that the overall chemical structure of the coal samples does not change significantly after the experimental treatment. X‐ray photoelectron spectroscopy analysis showed that the intensity of organic sulfur in coal samples is weakened after microwave irradiation, the characteristic peaks of thiols and thioethers are reduced to a great extent, and an increase in the intensity of sulfoxide organic sulfur is observed. On the basis of the results of experimental analysis and quantum chemical simulation calculations, the mechanism of organosulfur structure removal under the action of microwave is revealed.